Effect of Gas Adsorption on the Application of the Pulse-Decay Technique - Shaicheng Shen; Xiaochun Li; Zhiming Fang; Nao Shen (Geofluids)
The permeability of coal is an indispensable parameter for predicting the coalbed methane (CBM) and enhanced CBM (ECBM) production. Considering the low permeability characteristics of coal, the permeability is usually measured by the transient technique in the laboratory. Normally, it is assumed that the calculated permeability will not greatly vary if the pulse pressure applied in the experiment is small (less than 10% of pore pressure) and previous studies have not focused on the effect of the pulse pressure on the measurement permeability. However, for sorptive rock, such as coals and shales, the sorption effect may cause different measurement results under different pulse pressures. In this study, both nonadsorbing gas (helium) and adsorbing gas (carbon dioxide) were used to investigate the adsorption effect on the gas permeability of coal measurement with the pulse-decay technique. A series of experiments under different pore pressures and pulse pressures was performed, and the carbon dioxide permeability was calculated by both Cui et al.’s and Jones’ methods. The results show that the carbon dioxide permeability calculated by Jones’ method was underestimated because the adsorption effect was not considered. In addition, by comparing the helium and carbon dioxide permeabilities under different pulse pressures, we found that the carbon dioxide permeability of coal was more sensitive to the pulse pressure due to the adsorption effect. Thus, to obtain the accurate permeability of coal, the effect of adsorption should be considered when measuring the permeability of adsorptive media with adsorbing gas by the transient technique, and more effort is required to eliminate the effect of the pulse pressure on the measured permeability.